ATOMS: ALMA Three-millimeter Observations of Massive Star-forming regions – IV. Radio recombination lines and evolution of star formation efficiencies. Issue 4 (11th November 2021) - Zhang, C; Evans, Neal J; Liu, T; Wu, J-W; Wang, Ke; Liu, H-L; Zhu, F-Y; Ren, Z-Y; Dewangan, L K; Lee, Chang Won; Li, Shanghuo; Bronfman, L; et al.
ABSTRACT: We report the detection of radio recombination line (RRL) H40α towards 75 sources, with data obtained from ACA (Atacama Compact 7 m Array) observations in the ATOMS (ALMA Three-millimeter Observations of Massive Star-forming regions) survey of 146 active Galactic star-forming regions. We calculated ionized gas mass and star formation rate (SFR) with H40α line emission. The mass of ionized gas is significantly smaller than molecular gas mass, indicating that ionized gas is negligible in the star-forming clumps of the ATOMS sample. The SFR estimated with RRL H40α agrees well with that calculated with the total bolometric luminosity ( L bol ) when SFR ≥ 5 M⊙ Myr −1, suggesting that millimetre RRLs could well sample the upper part of the initial mass function and thus be good tracers of SFR. We also study the relationships between L bol and the molecular line luminosities ( L $^{^{′ }}_{\rm mol}$ ) of CS J = 2–1 and HC3 N J = 11–10 for all the 146 ATOMS sources. The $L_{\rm bol} \!-\! L^{′ }_{\rm mol}$ correlations of both the CS J = 2–1 and HC3 N J = 11–10 lines appear approximately linear and these transitions have success in predicting L bol similar to that of more commonly used transitions. The L bol -to-$L^{′ }_{\rm mol}$ ratios or SFR-to-mass ratios (star formation efficiency) do not change with galactocentric distances ( R GC ). Sources with H40α emission (or H ii regions) show higher L bol -to-$L^{′ }_{\rm mol}$ ratios than those without H40α emission, which may be an evolutionary effect.